Wide stopband single‐/dual‐bandpass filters using rotational symmetric composite right/left‐handed resonators. Issue 1 (January 2017) - Guo, Zhi‐Gui; Yang, Guo‐Min
ABSTRACT: Both single‐/dual‐bandpass wide stopband filters with rotational symmetry using composite right/left‐handed resonators are proposed in this study. Designs of this type obtain a single passband at 2.40 GHz as well as dual passbands at 2.40 and 5.20 GHz, and achieve a wide stopband with no additional structures, which are implemented and demonstrated with full‐wave simulations and measurements. Standing wave coupling models are presented to analyze the characteristics of a wide stopband effectively. The proposed single‐bandpass filter (BPF) with rotational symmetry achieves a preferable wide stopband, in which | S 21 | is mainly <−20 dB below 19.00 GHz; the proposed dual‐BPF also obtains a wide stopband, in which | S 21 | < −20 dB below 16.90 GHz. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:49–53, 2017